2009
DOI: 10.1104/pp.108.133744
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Genetic Evidence for the Key Role of AtCaM3 in Heat-Shock Signal Transduction in Arabidopsis    

Abstract: Heat shock (HS) is a common form of stress suffered by plants. It has been proposed that calmodulin (CaM) is involved in HS signal transduction, but direct evidence has been lacking. To investigate the potential regulatory function of CaM in the HS signal transduction pathway, T-DNA knockout mutants for AtCaM2, AtCaM3, and AtCaM4 were obtained and their thermotolerance tested. Of the three knockout mutant plants, there were no differences compared with wild-type plants under normal conditions. However, the AtC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
180
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(190 citation statements)
references
References 74 publications
7
180
1
Order By: Relevance
“…The role of WRKY39 as a positive regulator in thermotolerance is also consistent with possible regulation of WRKY39 by calcium, a second messenger in A. thaliana. Calmodulin (CaM) interacts with the WRKY39 protein (Park et al, 2005) and calcium is involved in HS in plants through CaM (Liu et al, 2008;Zhang et al, 2009). Calcium does not appear to be involved in the classic HS signaling pathways, i.e.…”
Section: Galley Proofmentioning
confidence: 99%
“…The role of WRKY39 as a positive regulator in thermotolerance is also consistent with possible regulation of WRKY39 by calcium, a second messenger in A. thaliana. Calmodulin (CaM) interacts with the WRKY39 protein (Park et al, 2005) and calcium is involved in HS in plants through CaM (Liu et al, 2008;Zhang et al, 2009). Calcium does not appear to be involved in the classic HS signaling pathways, i.e.…”
Section: Galley Proofmentioning
confidence: 99%
“…Phenotypic analysis showed that in normal growth conditions, atcam2-2 plants were indistinguishable from the wild type, while genetic analysis showed a reduced transmission of the atcam2-2 allele through the male gametophyte, and in vitro pollen germination revealed a reduced level of germination in comparison with the wild type. However, the atcam3 knockout mutant showed a clear reduction in thermotolerance after heat treatment at 45°C for 50 min (Zhang et al, 2009). Overexpression of AtCaM3 in either the atcam3 knockout or wild-type background significantly rescued or increased the thermotolerance, respectively.…”
mentioning
confidence: 99%
“…Interestingly, Zhang and colleagues found that while the thermotolerance of the cam3 knockout mutant was significantly reduced after the heat-shock treatment, cam2 seedlings showed a thermotolerance similar to the wild type (Zhang et al 2009). Taken together these results suggest the existence of a functional diversification not only for genes encoding different CAM isoforms (CAM3 and CAM7) but also for genes encoding for the same isoform (CAM3 and CAM2).…”
Section: Introductionmentioning
confidence: 99%
“…In Arabidopsis, only two members of this gene family have been functionally characterized, CAM3 (Zhang et al 2009) and CAM7 (Kushwaha et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation